Statistical modelling and optimisation of the factors affecting the surface roughness of C45 steel treated by the centrifugal disk mass finishing process. (30th January 2020) - Djender, K.; Hamouda, K.; Keddam, M.; Amrou, M.H.E.
The goal of this study was to find the optimal conditions for improving the surface roughness (Ra) of the C45 steel treated by the centrifugal disk mass finishing process. The factors selected were the grain size of the abrasive media ( Gs ), the rotational speed of the disc ( ω ) and the loading volume (V). In order to optimize its parameters and describe the variation of ( Ra ), a regression model was developed with the response surface methodology. The model was validated with the analysis of variance with a descriptive quality estimated to 98%. The Student test was used to improve the model by neglecting the terms having an insignificant influence. Experimental tests demonstrated that the error between the estimated and the experimentally values did not exceed 2.34%. The lowest roughness value Ra = 1.079 m was obtained analytically by the optimal values of Gs = 4 and ω = 241.8 rpm.